Using an Ionic Liquid as the Porogen in the Preparation of Methacrylate-Based Monolith in Capillary Liquid Chromatography - Chen Na; Chen Jun; Liu Kun-Feng; Bai Lian-Yang; Zhang Yu-Ping (Adsorption Science & Technology)
A methacrylate monolith was prepared inside a fused silica capillary column by microwave irradiation using an ionic liquid (1-hexyl-3-methylimidazolium tetrafluoroborate) as the porogenic solvent. Baseline separation of the model analytes, including thiourea, benzene, toluene, ethylbenzene and propylbenzene, was achieved by capillary liquid chromatography, with the lowest theoretical plate height of 26.83 µm for benzene. In addition, we also investigated the effects of the acetonitrile content in the mobile phase, flow rate on retention time, resolution and total porosity. The morphology of methacrylate monolith was studied by scanning electron microscopy.